ANALISA FAKTOR YANG MEMPENGARUHI NYERI MENSTRUASI PADA REMAJA PUTRI - Sartika S, Titin Dewi; Rahmadhani, Sendy Pratiwi; Riski, Merisa (JURNAL KESEHATAN TERAPAN, 2021)
Background: dysmenorrhea during menstruation can cause activity disorders such as high levels of absence from school and work, limitations in social life, academic performance, and sports activities and even psychologically, people with dysmenorrhea often experience irritable, irritable, unable to concentrate, difficulty sleeping, tired, and feeling depressed, at school they also experience emotional changes with the occurrence of a sensitive nature to the words of teachers and friends. This study aims to determine the factors that influence the occurrence of menstrual pain. questionnaire on adolescents who experienced menstrual pain during the period February 2020. This type of research is in. The sample was selected by simple random sampling by fulfilling the inclusion and exclusion criteria so that a sample of 54 girls with dysmenorrhea was obtained. Statistical test using chi square test with p value <0.05 was considered statistically significant. The results showed that there was a relationship between body weight and menstrual pain, there was a relationship between menarche and menstrual pain, there was a relationship between age and menstrual pain, and there was a relationship with family history and menstrual pain. The conclusion of this study is that there is a significant relationship between body weight, menarche and mPrimary dysmenorrhea is a physiological thing in women of childbearing age, but young women who experience enstrual pain. Keywords: Age, body weight, menarche, dysmenorrhea